Maternal mortality in Panama from 1998 to 2022 - Yovani Chavez; Tania Herrera (Pan American Health Organization, 2024)
Objective. To examine maternal mortality in Panama, analyzing its direct obstetric deaths, indirect obstetric deaths, and contributory conditions. Methods. This cohort study used publicly available data from the National Institute of Statistics and Census to present a 25-year retrospective analysis of maternal deaths in the Republic of Panama from 1998 to 2022. Public data were sourced from the National Institute of Statistics and Census website of Panama. Relevant codes from the International Statistical Classification of Diseases and Related Health Problems, Tenth Revision (ICD) were used. The maternal mortality ratio (MMR) was defined as the number of maternal deaths per 100 000 live births. Trendline reliability with R2 was performed to analyze the data. Results. A total of 1 026 maternal deaths occurred in Panama from 1998 through 2022, of which 61.2% were attributed to direct obstetric causes; 23.9%, indirect obstetric causes; 13.6%, contributory conditions; and 1.4% were unknown or undetermined. The average MMR was 60.1. The trendline reliability resulted in R2 = 0.1 (y = -0.5147x + 1094.7), which is not statistically significant but meets the 2030 Sustainable Development Goals. The specific primary causes of direct obstetric deaths were: 12.9% due to postpartum hemorrhage (ICD O72); 9.2%, eclampsia (ICD O15); 6.7%, puerperal sepsis (ICD O85); and 6.3%, pre-eclampsia (ICD O14). For indirect obstetric deaths, the primary causes were: 14.9% due to other maternal diseases classifiable elsewhere but complicating pregnancy, childbirth, and the puerperium (ICD O99); and 7.3%, maternal infectious and parasitic diseases classifiable elsewhere but complicating pregnancy, childbirth, and the puerperium (ICD O98). Conclusions. The findings of this study confirmed that there were substantially more direct obstetric causes (61.2%) than indirect obstetric causes (23.9%), contributory causes (13.6%), or unknown/undetermined causes (1.4%) of maternal mortality, despite being highly preventable. Although Panama is right on track to fulfill the target of 70 MMR by 2030, these results highlight the lack of health care access due to the absence of obstetrician-gynecologists per 100 000 population in indigenous comarcas, where 30.8% of the maternal mortalities occur. Furthermore, the health system in Panama is not immune to pandemics and crises. From 1998 to 2022, there were 5 years when the MMR in Panama exceeded 70: 2001, 2002, 2006, 2011, and 2020. These findings also underscore the dichotomy between statistics and health policy. While the trendline reliability was insignificant (R2 = 0.1), the MMR satisfies requirements for the 2030 Sustainable Development Goals. Future studies should consider factors related to indirect obstetrics and contributory causes of deaths, health care access, COVID-19, cesarean section and natural birth, age, economic income, prenatal and postpartum care, as well as the quality of private and public health facilities in the Americas.